Spatiality, Place and Territory: an Outline of Landscape and its Experience - Matti, Felipe Andres (2025)
This paper explores the aesthetic experience of landscape through the conceptual triad of space, territory, and Earth. It argues that territory is the semiotic structuration of space, while landscape remains unassimilated, operating as a site of desubjectification and spatial openness. The study examines how deterritorialization and landscapification disrupt dominant spatial regimes, allowing new forms of spatial relation to emerge. The paper contends that access to landscape is essential for the possibility of otherness and spatial transformation, particularly for marginalized groups, and that the experience of landscape grounds the potential for rethinking spatiality beyond institutional constraints.